2021
DOI: 10.1016/j.trsl.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The von Hippel–Lindau Cullin-RING E3 ubiquitin ligase regulates APOBEC3 cytidine deaminases

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
1
5
0
Order By: Relevance
“…A3B protein levels are increased by epoxomicin treatment in mock-, B3-and C2-infected conditions (Fig 7E). These observations are consistent with work by Scholte ´s and colleagues identifying proteasomal activity as a post-translational mechanism regulating the amounts of A3 proteins [27]. We conclude that A3B degradation takes place both in mock-, B3-and C2-infected cells and that this degradation is dependent of the proteasome.…”
Section: Plos Pathogenssupporting
confidence: 93%
“…A3B protein levels are increased by epoxomicin treatment in mock-, B3-and C2-infected conditions (Fig 7E). These observations are consistent with work by Scholte ´s and colleagues identifying proteasomal activity as a post-translational mechanism regulating the amounts of A3 proteins [27]. We conclude that A3B degradation takes place both in mock-, B3-and C2-infected cells and that this degradation is dependent of the proteasome.…”
Section: Plos Pathogenssupporting
confidence: 93%
“…Supporting the role of the HIF transcription factor in controlling AID expression, it has been shown that the inactivation of pVHL leads to a strong accumulation of the HIF‐1α protein, and consequently to increased protein levels of the members of the APOBEC3 cytidine deaminase (A3B) family, which includes AID [13]. Thus, we would have expected that inactivation of pVHL would lead to enhanced HIF‐dependent transcriptional activity [13], resulting in increased production of the AID mRNA and protein and more efficient CSR and SHM in a hypoxic environment in the GC or in response to cytokine signaling. Nevertheless, a B‐cell‐specific KO of pVHL, which resulted in constitutive HIF‐1α stabilization [6, 13], surprisingly led to impaired affinity maturation and defective CSR [6].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we would have expected that inactivation of pVHL would lead to enhanced HIF‐dependent transcriptional activity [13], resulting in increased production of the AID mRNA and protein and more efficient CSR and SHM in a hypoxic environment in the GC or in response to cytokine signaling. Nevertheless, a B‐cell‐specific KO of pVHL, which resulted in constitutive HIF‐1α stabilization [6, 13], surprisingly led to impaired affinity maturation and defective CSR [6]. These results highlight the underlying difficulty of exploring the role of hypoxia and HIF in antibody diversification in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Human hepatocytes containing UBE2L3 polymorphisms have been found to be more susceptible to hepatitis B viral infection due to increased proteasome-mediated degradation of A3A ( 22 ). Additionally, multiple overexpressed APOBEC3 family members have been shown to be controlled by the activity of ubiquitin ligase complexes containing von Hippel–Lindau tumor suppressor protein (pVHL) and ariadne RING-in-between-RING E3 ubiquitin protein ligase 1 (ARIH1) ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reduced activity of the F-box protein, FBXO22, contributes to tumor progression and metastasis in lung and breast cancers by increasing levels of key oncogenic factors such as Bach1, HDM2 and SNAIL ( 33 ). Since APOBEC3 protein abundance has been shown to be controlled by proteasome activity in human embryonic kidney cells ( 23 ), somatically acquired alterations in such ubiquitin-proteasome pathway factors may similarly cause changes in A3A protein abundance leading to enhanced cancer cell mutagenesis.…”
Section: Introductionmentioning
confidence: 99%